Gear Meshing State Detection Based on Phase Vibration Measurement Technology - Rong Rong; Shi Dapeng; Wang Zhuo; Zhang Xu; Ding Xiaoyu (Jixie chuandong)
In order to solve the problem that the detection of gear meshing state requires a large number of data samples, a gear meshing state detection method based on phase vibration measurement technology is proposed. This method uses a camera to shoot a gearbox, extracts vibration signals at multiple locations from the captured video, establishes time-frequency domain features for the vibration signals, and finally uses random forest classification to complete the detection. An open gearbox is taken as the object and the accuracy and effectiveness of the proposed method is proved through experiments.